The impact of HIV on the development of severe acute malnutrition in underfive children at UTH- Lusaka, Zambia - Chilonga, Charity M. (Lusaka: University of Zambia , School of Medicine, 2015)
Severe acute malnutrition (SAM) is on of the top five causes of morbidity and mortality among under five children in zambia and at the UTH, in particular with mortality being at 73% and morbidity at 76%. HIV one of the immediate causes of SAM is mainly acquired through mother to child transmission. The study was aimed at investigating the impact of HIV on the development of SAM in the under five children at the UTH.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Trace elements in nutrition; Malnutrition